2019
DOI: 10.3390/ijms20071682
|View full text |Cite
|
Sign up to set email alerts
|

Mel1c Mediated Monochromatic Light-Stimulated IGF-I Synthesis through the Intracellular Gαq/PKC/ERK Signaling Pathway

Abstract: Previous studies have demonstrated that monochromatic light affects plasma melatonin (MEL) levels, which in turn regulates hepatic insulin-like growth factor I (IGF-I) secretion via the Mel1c receptor. However, the intracellular signaling pathway initiated by Mel1c remains unclear. In this study, newly hatched broilers, including intact, sham operation, and pinealectomy groups, were exposed to either white (WL), red (RL), green (GL), or blue (BL) light for 14 days. Experiments in vivo showed that GL significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
(86 reference statements)
2
1
0
Order By: Relevance
“…In addition, we also observed that G→B and B→G significantly promoted the protein expression of p-PKC and p-ERK, and Mel1c may mediate a green and blue monochromatic light combination stimulated B-lymphocyte proliferation through the intracellular PKC/ERK signaling pathway. Consistent with our findings, Ning et al reported that melatonin promoted IGF-1 mRNA expression through the Mel1c-mediated PKC/ERK pathway in chick liver cells [ 52 ]. Interestingly, ERK is considered a signaling hub with many different input and output pathways with multiple crosstalks [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we also observed that G→B and B→G significantly promoted the protein expression of p-PKC and p-ERK, and Mel1c may mediate a green and blue monochromatic light combination stimulated B-lymphocyte proliferation through the intracellular PKC/ERK signaling pathway. Consistent with our findings, Ning et al reported that melatonin promoted IGF-1 mRNA expression through the Mel1c-mediated PKC/ERK pathway in chick liver cells [ 52 ]. Interestingly, ERK is considered a signaling hub with many different input and output pathways with multiple crosstalks [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed that G→B and B→G signi cantly promoted the protein expression of p-PKC and p-ERK protein, and Mel1c may mediate a green and blue monochromatic light combination stimulated B-lymphocyte proliferation through the intracellular PKC/ERK signaling pathway. Consistent with our ndings, Ning et al reported that melatonin promoted IGF-1 mRNA expression through Mel1c mediated-PKC/ERK pathway in chick liver cells [48]. Interestingly, ERK is considered a signaling hub with many different input and output pathways with multiple crosstalks [49].…”
Section: Role Of Melatonin Receptors In Melatonin-mediated a Combinatsupporting
confidence: 90%
“…Three types of melatonin membrane receptors have been identified: Mel1a (or MT1, ML1a, ML1, MTNR1a) and Mel1b (or MT2, ML1b, MTNR1b) receptor subtypes, which are present in humans and other mammals, while an additional melatonin receptor subtype, Mel1c (MTNR1C), has been identified in fishes, amphibians, and birds (Emet et al, 2016). Mel1a and Mel1b as GPCR bonded with Gαs to decrease cAMP, while Mel1c coupled with Gαq to activate the membrane-associated phospholipase C and protein kinase C pathways (Ning et al, 2019).…”
Section: Melatonin Receptorsmentioning
confidence: 99%